2007
DOI: 10.1007/s11103-007-9228-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of a monosaccharide transporter gene OsMST4 from rice (Oryza sativa L.)

Abstract: Monosaccharide transporters mediate the membrane transport of a variable range of monosaccharides, which plays a crucial role in sugar distribution throughout the plant. To investigate the significance of monosaccharide transporters for rice (Oryza sativa L.) seed development, cDNA of a new putative monosaccharide transporter gene OsMST4 was isolated. The deduced OsMST4 protein shows typical features of monosaccharide transporters, and shares high homology with other plant homologues. Heterologous expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 44 publications
1
46
0
1
Order By: Relevance
“…1; Supplemental Figs. S1 and S2; Büttner and Sauer, 2000;Wang et al, 2007). It shares especially high homology with the Arabidopsis genes AtSTP4, AtSTP9, and AtSTP11 and petunia gene Pmt1, which have been reported to be expressed mainly in pollen grain and the pollen tube ( Fig.…”
Section: Csht1 Is a Plasma Membrane Protein Expressed Specifically Inmentioning
confidence: 93%
See 1 more Smart Citation
“…1; Supplemental Figs. S1 and S2; Büttner and Sauer, 2000;Wang et al, 2007). It shares especially high homology with the Arabidopsis genes AtSTP4, AtSTP9, and AtSTP11 and petunia gene Pmt1, which have been reported to be expressed mainly in pollen grain and the pollen tube ( Fig.…”
Section: Csht1 Is a Plasma Membrane Protein Expressed Specifically Inmentioning
confidence: 93%
“…By contrast, pollen tubes of petunia (Petunia hybrida) grow equally well on medium containing Glc, Fru, or Suc (Ylstra et al, 1998). Although several hexose transporter genes are highly expressed in pollen grains or pollen tubes of Arabidopsis (Büttner, 2010) and rice (Oliver et al, 2007a;Wang et al, 2007Wang et al, , 2008, single knockouts of these genes do not result in a phenotype, and in vitro experiments demonstrate that the germination of Arabidopsis pollen seems to be strictly dependent on Suc in the medium. Addition of Glc causes instant bursting of Arabidopsis pollen tubes (Schneidereit et al, 2003(Schneidereit et al, , 2005Scholz-Starke et al, 2003).…”
mentioning
confidence: 99%
“…Similarly, Arabidopsis STP6 , STP9 (Schneidereit et al, 2003), and STP11 (Schneidereit et al, 2005) have been shown to be expressed during anther/pollen development. Also, several MSTs from rice have been demonstrated to play a crucial role in sugar distribution (Toyofuku et al, 2000;Ngampanya et al, 2003;Mamun et al, 2006;Wang et al, 2007Wang et al, , 2008b.…”
Section: Csa Controls Sugar Partitioning Into the Anthermentioning
confidence: 99%
“…The MST gene family in Arabidopsis is investigated in more detail than in other species. Up to now, six MSTs from rice (Toyofuku et al 2000;Ngampanya et al 2003;Mamun et al 2006;Wang et al 2007) and two from barley (Weschke et al 2003) have been studied, but MSTs from other cereals such maize and wheat have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Monosaccharide transporters expressed in both sink and source organs/tissues have also been found in tomato (Gear et al 2000), grapevine (Hayes et al 2007) and rice (Toyofuku et al 2000;Wang et al 2007). The Arabidopsis AtSTP3 is the only MST speciWcally expressed in source organs/tissues .…”
Section: Introductionmentioning
confidence: 99%